Analisis Akad Istishna dalam Transaksi Jual-Beli Alat Kesehatan pada PT. Dwi Utama Medika - Humairoh Rahmadhani Fitri; Dian Sugiarti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Buying and selling transactions are an effort to support economic growth. One of the Muamalah contracts that is in accordance with sharia economic principles is the Istishna contract. This research aims to evaluate and analyze the implementation of the Istishna Agreement in Muamalah at PT. Dwi Utama Medika, which is in harmony with Islamic economics. The Istishna contract is a valid contract in Islam, namely a buying and selling transaction process between consumers (Mustashni') and producers (Shani') to produce a product according to the specifications of the goods determined by the consumer (Mustashni'). The method used by researchers is a qualitative approach using triangulation techniques to collect data through in-depth interviews, observation, and documentation. The samples or data sources identified in this research are managers, employees, and consumers. The result of the research is the implementation of the Istishna agreement at PT. Dwi Utama Medika, which complies with sharia principles based on the Koran, As-Sunnah, and DSN-MUI Fatwa. The importance of this research is as a reference or information for stakeholders and other stakeholders regarding the implementation of business according to sharia principles, especially in the health sector. It is hoped that the Istishna Agreement can be a solution to sharia financing obstacles. In this way, the public can pay more attention and interest to the Istishna contract, which is in accordance with Islamic principles.